USING MASS MEDIA IN LEARNING ENGLISH - Qurbanova Marjona; Abdusamadov Zafar (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article deals with the opportunities which mass media is creating for people who are learning English. It also gives information about the types of mass media and how to use them effectively while spending time for a foreign language.